Pembinaan Tukang Mengenai Sambungan Baja Pada Bangunan Gedung di Kecamatan Sekarbela Kota Mataram - Fathmah Mahmud; Hariyadi Hariyadi; I Nyoman Merdana; Ngudiyono Ngudiyono; Ni Nyoman Kencanawati (Universitas Mataram, 2023)
The availability of land for the residential area is becoming scarce in Mataram, The capital city of West Nusa Tenggara. In response to this situation, the construction of high buildings becoming a trend. A trend that initiating a new quandary as this city is located in a high-risk area, prone to earthquakes. Still fresh in our memory, when this area was struck by a series of earthquakes in 2018, two major shocks of 7 and 6,9 magnitude were followed by thousands of aftershocks. Therefore, means are needed to mitigate the risk, for instance reinforcing the utilization of steel. Steel is known for its capacity to withhold immense quakes. Melted connecting plates and cracked connecting bolts are frequent issues in high building construction, often leading to the faulty building. Hence, educating craftsmen on steel structure connection is essential. This community service is done by training craftsmen after acquiring data regarding their capabilities. On the training day, craftsmen were taught by the community service team regarding frame connection, column beam connection, the connection of sub-beam main beam, and base plate connection. The craftsmen are given time to discuss with the community service team. The evaluation shows, there is an increase in craftsmen performance scores after receiving the training, there was an increase of 44,74 or equivalent to 112,225%.